PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA TENAGA PERAWATAN LOKOMOTIF BALAI YASA YOGYAKARTA (FSTPT Indonesia, 2023)
A study was conducted to find out the effect of occupational safety and health on the work productivity of the Balai Yasa Yogyakarta locomotive maintenance staff. This study was conducted with the aim to know the variable effect of the Occupational Health and Safety (OHS) toward the productivity variable of the locomotive maintenance staff of Balai Yasa Yogyakarta. This research is quantitative research with the independent variable being occupational Health and Safety (OHS) and the dependent variable being work productivity. This study uses a non-probability sampling data collection technique with incidental sampling technique obtained through 74 respondents of Balai Yasa Yogyakarta locomotive maintenance personnel obtained through the calculation using Slovin formula with data collection methods using questionnaires. The method used in this research is multiple linear regression. The results of this study were obtained through data analysis that was carried out using the IBM SPSS 26 program application, which showed that occupational safety (X1) had a significant effect on work productivity, and occupational health (X2) did not have a significant effect on work productivity. So as simultaneously, the results of the F test calculations have a significant effect on the work productivity (Y) of the locomotive maintenance staff of Balai Yasa Yogyakarta. ABSTRAKPenelitian ini dilakukan dengan tujuan untuk mengetahui pengaruh K3 terhadap produktivitas kerja tenaga perawatan lokomotif Balai Yasa Yogyakarta. Penelitian ini merupakan penelitian kuantitatif dengan variabel bebas keselamatan kerja dan kesehatan kerja serta dengan variabel terikat produktivitas kerja. Penelitian ini menggunakan teknik pengumpulan data sampling non probability sampling yang diperoleh melalui 74 responden tenaga perawatan lokomotif Balai Yasa Yogyakarta yang didapat melalui perhitungan rumus slovin dengan metode pengumpulan data menggunakan kuesioner. Metode yang digunakan dalam penelitian ini adalah regresi linier berganda. Hasil dari penelitian ini didapat melalui analisis data yang dilakukan menggunakan aplikasi program IBM SPSS 26 yang menunjukkan bahwa keselamatan kerja (X1) berpengaruh signifikan terhadap produktivitas kerja, sementara kesehatan kerja (X2) tidak berpengaruh signifikan terhadap produktivitas kerja. Secara simultan melalui hasil perhitungan uji F mempunyai pengaruh yang signifikan terhadap produktivitas kerja (Y) tenaga perawatan lokomotif Balai Yasa Yogyakarta.